PUSAT KEGIATAN LANSIA (SENIOR CENTER) DI KOTA PONTIANAK - Miftahulhadi, Annisa Salsabilla; Pebriano, Valentinus; Purnomo, Yudi (JMARS: Jurnal Mosaik Arsitektur, 2024)
Elderly people is someone who has reached the age of 60 years and above. The elderly experience a decrease in organ function, physical and psychological conditions that cause them to not be optimal in meeting their life needs. Despite their declining body condition, the elderly must remain active and socialize. The activity area of the elderly group is different from the productive age group because there are many physical and psychological changes. As life expectancy increases, the Pontianak City Government is aggressively making efforts to maintain the social welfare level of the elderly. On the other hand, a special place for Elderly activities is not yet available. The design of the senior center aims to create a place for senior activities that meets the design standards. The design method uses four steps, namely determining the design object, types and techniques of data collection, analysis, synthesis, and preparation of design stages. Data is obtained from surveys and interviews (primary data), literature studies and precedent studies (secondary data). The result of the design of the senior center is a building design that pays attention to the physical and psychological comfort of the elderly. The design area has 5 masses, namely the reception building, health building, library, hall, and service building. The senior center is expected to be a solution to meet the needs of elderly activities so that physical and mental health is maintained, and can be empowered so that their level of welfare is more secure.Keywords: Elderly, activity, senior center